Factors Affecting Construction Organization Quality Management System In The Malaysian Construction Industry - Said, Ilias; Ayub, Abd Rahman; Abd Razaki, Arman; Tee, Kuan Kooi (2009)
The main focus of the construction industry is to ensure that projects are successfully completed within the constraints of best quality, stated period and at minimum cost possible.